2002
DOI: 10.1029/2002gl015387
|View full text |Cite
|
Sign up to set email alerts
|

Variations on the concentration of 222Rn in the subsurface of the volcanic island of Tenerife, Canary Islands

Abstract: A simple theoretical model, based on the assumption that radon is transported by molecular diffusion combined with advective flow induced by barometric pressure, is used to investigate radon exhalation at three subsurface monitoring sites in the volcanic island of Tenerife, Canary Islands. The model is intended to filter out all known contributions to radon flux, in an attempt to find potential precursory signals of seismic and/or volcanic activity. For the period of observations (1 December 2000 to 1 April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…In underground environments, radon-222 concentration is often characterized by large temporal variation, mainly caused by seasonal changes in natural ventilation (Wilkening and Watkins, 1976) and by atmospheric pressure variation (Clements and Wilkening, 1974;Eff-Darwich et al, 2002;Viñ as et al, 2007). Other causes of transient temporal variation have been reported, such as water infiltration (Perrier et al, 2007) or hydromechanical effects in the vicinity of an artificial lake (Trique et al, 1999;Richon et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…In underground environments, radon-222 concentration is often characterized by large temporal variation, mainly caused by seasonal changes in natural ventilation (Wilkening and Watkins, 1976) and by atmospheric pressure variation (Clements and Wilkening, 1974;Eff-Darwich et al, 2002;Viñ as et al, 2007). Other causes of transient temporal variation have been reported, such as water infiltration (Perrier et al, 2007) or hydromechanical effects in the vicinity of an artificial lake (Trique et al, 1999;Richon et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…At these levels, the air pressure regime is related to the local atmospheric barometric pressure while temperature tends to show stabile patterns reflecting the rock temperature at depth. Radon signals characterized by systematical recurrence of patterns in the temporal, geological and geographical domains have been reported from tunnels and boreholes in France [10], from Tenerife at a depth of more than 800 m [11][12][13] and from the desert in Israel at a depth of more than 100 m [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…They exhibited similar temporal variations that are well correlated to temporal changes in barometric pressure. EFF-DARWICH et al (2002) showed that the observed behaviour of the radon signal is explained by the pumping effect of temporal changes in barometric pressure. Considering that CO 2 and Radon present similar behaviour (see Fig.…”
Section: Resultsmentioning
confidence: 99%